Pengaruh Model Pembelajaran Problem Based Learning (PBL) Berbantuan LKPD terhadap Kemampuan Berpikir Kritis Peserta Didik - Sonia Nurul Ayunda; Lufri Lufri; Heffi Alberida (Journal on Education, 2023)
The teacher is a factor that can directly influence quality improvement in improving the quality of education and students' critical thinking skills. Teachers are responsible for encouraging and guiding students to become proficient in active critical thinking and enjoy learning. The teacher is also responsible for all things in the class and provides assistance such as supporting the stages so that students can develop. A process so that teaching and learning activities in the classroom turn interactive and achieve the objectives of the teaching and learning activities is to use a learning model. An example of a learning model in order to improve students' critical thinking skills is a problem-based learning model. This research methodology is based on seven steps of literature search: determining the purpose of writing, selecting database sources, selecting keywords at the stage of searching a database, carrying out the stages of searching for literature, and determining the inclusion criteria for the articles used. selected according to inclusion characteristics and synthesis results in 20 national and international journals. The purpose of this study was to test the effect of the problem-based learning model (PBL) assisted by worksheets on students' thinking skills. The results of the study found that the problem-based learning model supported by LKPD was effective in increasing students' critical thinking skills.